2012
DOI: 10.1142/s0217732312500757
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutativity and Non-Anticommutativity Perturbative Quantum Gravity

Abstract: In this paper we will study perturbative quantum gravity on supermanifolds with both noncommutative and non-anticommutative coordinates. We shall first analyses the BRST and the anti-BRST symmetries of this theory. Then we will also analyze the effect of shifting all the fields of this theory in background field method. We will construct a Lagrangian density which apart from being invariant under the extended BRST transformations is also invariant under on-shell extended anti-BRST transformations. This will be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…This is because both of these theories are based on modifying the usual energy-momentum dispersion relation in the UV limit such that it reduces to the usual energy-momentum dispersion relation in the IR limit. It may be noted that such a modification of the usual energy-momentum has also been obtained in discrete spacetime [15], spacetime foam [16], the spin-network in loop quantum gravity (LQG) [17], ghost condensation [18], and non-commutative geometry [19,20]. The non-commutative geometry occurs due to background fluxes in string theory [21,22], and it is used to derive one of the most important rainbow functions in gravity's rainbow [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…This is because both of these theories are based on modifying the usual energy-momentum dispersion relation in the UV limit such that it reduces to the usual energy-momentum dispersion relation in the IR limit. It may be noted that such a modification of the usual energy-momentum has also been obtained in discrete spacetime [15], spacetime foam [16], the spin-network in loop quantum gravity (LQG) [17], ghost condensation [18], and non-commutative geometry [19,20]. The non-commutative geometry occurs due to background fluxes in string theory [21,22], and it is used to derive one of the most important rainbow functions in gravity's rainbow [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…This is because both these UV completions of General Relativity are based on the modification of the usual energy-momentum dispersion relation in the UV limit, such that it reduces to the usual energy-momentum dispersion relation in the IR limit. Furthermore, such a modification of the energy-momentum relation also occurs in ghost condensation [41] and non-commutative geometry [7,42]. It may be noted that non-commutative geometry occurs due to background fluxes in string theory [43,44].…”
Section: Introductionmentioning
confidence: 97%
“…Since a e-mail: hendi@shirazu.ac.ir b e-mail: sh.panahiyan@gmail.com c e-mail: behzad.eslampanah@gmail.com d e-mail: momennia1988@gmail.com the standard energy-momentum dispersion relation enjoys the Lorentz symmetry, it is expected to modify this relation in the ultraviolet limit. In fact, it has been observed that such a modification to the standard energy-momentum relation occurs in some models based on string theory [1], the spin network in loop quantum gravity (LQG) [2], spacetime foam [4], the discrete spacetime [5], Horava-Lifshitz gravity [11,12], ghost condensation [13], non-commutative geometry [3,14], and doubly special relativity.…”
Section: Introductionmentioning
confidence: 99%